Efektivitas Nasi Beras, Merah (Oryza Nivara) Terhadap Kadar Kolesterol Total Penderita Diperkolesterolemia - Nonce Nova Legi; Mirna Kawulusan; Marstevi Olivia Gedoan (POLTEKKES KEMENKES MANADO, 2019)
Hypercholesterolemia is an increase in total cholesterol levels in the blood beyond the normal limits. Excess cholesterol levels in the blood will have an impact on degenerative diseases. Brown rice (oryza nivara) is a rice rich in vitamins, minerals and contain water soluble fiber that can help bind cholesterol, then throw it out of the body. Regular consumption of brown rice is very beneficial for health that can reduce levels of LDL. The aim of this research is to know the effectiveness of brown rice rice to total cholesterol level in hypercholesterolemia patient in Vilage Sea Pineleng District of Minahasa Regency. The type of this research is Quasi Eksperimen with One Group of Pretest and Posttest Design. The sample in this study is the entire population of hypercholesterolemia patients recorded in Posbindu Village Sea Pineleng District Minahasa regency that meets the inclusion criteria. Rice brown rice is given for 8 consecutive days every morning, day and night. Total cholesterol levels were measured before and after administration of brown rice. Data analysis using Paired t-test. The results showed that the total cholesterol level before the study was the highest of 360 mg / dl, the lowest was 216 mg / dl, and after the highest total cholesterol was 298 mg / dl, the lowest was 164 mg / dl. The result of statistical test shows that p = 0,019 (p <0,05), which means that there is difference of total cholesterol before and after giving of rice of red rice to hypercholesterolemia patient in Vilage Sea Pineleng Sub-district of Minahasa Regency.